ADDITIONAL COSTS AS A CONDITION OF COMPLETING SELL PURCHASE TRANSACTIONS THRIFTING INSTAGRAM ACCOUNT @THRIFT.PEREMPUAN WAHBAH AZ ZUHAILI'S PERSPECTIVE - Rahmad, Nasnurdin; Permata, Cahaya (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
In buying and selling used clothing or thrifting, sellers often provide promos for the items being sold. However, there are cases where the buyer is required to add a fee to complete the sale and purchase of the promo, if this is not fulfilled the product will not be sent or the transaction will not be completed. This study aims to find out the practice of adding thrifting buying and selling fees on the @thrift.perempuan account, the additional factors and the law of adding fees as a settlement of buying and selling transactions according to Wahbah Az-Zuhaili. This type of research is empirical juridical research with a conceptual approach and living case studies. Data was collected by interview, observation and document study then the data was processed using qualitative methods with a deductive thinking approach. The results of this study indicate that the concept of conditional buying and selling with additional fees on the @thrift.perempuan account, in Wahbah Az-Zuhaili's opinion, is a fasid sale and purchase because there is no element of honesty from one party and harms the other party